2010
DOI: 10.1111/j.1521-0391.2010.00031.x
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis Use Correlates of Syringe Sharing among Injection Drug Users

Abstract: This study examines whether the relation between acute cannabis use and syringe sharing during single injection days is similar among regular and non-regular users, participating in a cohort study of injection drug users in Montréal, Canada. 236 (36.6%) subjects were classified as regular cannabis users (RCUs), 227 (35.2%) as non-regular cannabis users (NRCUs) and 181 (28.1%) were abstinent. Cannabis use during a single injection day was associated with a fivefold increased risk of sharing (OR 4.92; in NRCUs c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 30 publications
1
13
0
1
Order By: Relevance
“…In the current study, HIV-infected Russian “recent past” users do not behave exactly like current or non-users and hence timing of use merits closer examination. Another study classified non-HIV-infected individuals as regular and non-regular cannabis users and examined syringe sharing (Jutras-Aswad et al, 2010). This study revealed that on the day when participants used cannabis, non-regular cannabis users were five times more likely to share syringes than regular cannabis users.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, HIV-infected Russian “recent past” users do not behave exactly like current or non-users and hence timing of use merits closer examination. Another study classified non-HIV-infected individuals as regular and non-regular cannabis users and examined syringe sharing (Jutras-Aswad et al, 2010). This study revealed that on the day when participants used cannabis, non-regular cannabis users were five times more likely to share syringes than regular cannabis users.…”
Section: Discussionmentioning
confidence: 99%
“…À court terme, les effets cognitifs de la marijuana inhalée apparaissent à une concentration sérique entreTous droits réservés © Drogues, santé et société, vol. 16, no 1, mars 2018 de l'impulsivité, une difficulté de résolution de problèmes et une plus grande prise de risque ont été notées chez les utilisateurs occasionnels (Desrosiers, Ramaekers, Chauchard, Gorelick et Huestis, 2015 ;Jutras-Aswad, Zang et Bruneau, 2010). Ceux-ci seraient plus sujets à être impliqués dans des accidents routiers (Desrosiers, Ramaekers, Chaunard, Gorelick et Huestis, 2015 ;Eksborg et Rajs, 2008).…”
Section: Facteurs Modulant L'association Entre L'exposition Au Cannabunclassified
“…This poly-substance pattern of use has prompted researchers to investigate the potential interaction with, and effect of, these drug on neuropsycho-biological processes related to addiction. For example, some studies reveal that cannabis consumption enhances the incentive to use cocaine in individuals dependent on both, while others suggested that cannabis reduced withdrawal symptoms in abstinent cocaine-addicted subjects (22, 90, 91). Although it is recognized that components of the ECBS are involved in cocaine-seeking behaviors, very few studies have focused on understanding the neural and behavioral effects of endogenous and exogenous cannabinoids on psychostimulant use.…”
Section: The Endocannabinoid Systemmentioning
confidence: 99%
“…Results from this study suggest that smoking cannabis reduced the achievement of sustained remission and increased relapse to cocaine use (91) (see Table 1). Surprisingly, a study from Jutras-Aswad et al supports the assumption that irregular cannabis use increases risky behaviors (syringe sharing) of cocaine and opioid users, as opposed to regular cannabis use, suggesting a complex dose-effect relationship between cannabis and addictive behaviors (22). The possibility that cannabis use by recently abstinent cocaine-dependent individuals influences relapse to drug and other related behaviors remains poorly documented.…”
Section: Interaction Of the Ecbs With Biological And Behavioral Corrementioning
confidence: 99%
See 1 more Smart Citation